Audit publicity and tax compliance: A quasinatural experiment - Pietro Battiston; Denvil Duncan; Simona Gamba; Alessandro Santoro (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2016)
We use confidential data on Value Added Tax payments at the sector level, in two large Italian cities, to estimate the effect of audits publicity on tax compliance of local sellers. By employing a Difference-in-Differences identification strategy, we find that such publicity has a positive effect on fiscal declarations made shortly after. The results suggest that increasing awareness on future audits via the media can be an important instrument in the hands of tax authorities.
Keywords: H26; K34; K40; 330; Tax evasion; Quasi-natural experiment; Audit publicity